2010
DOI: 10.1007/s11433-010-4160-5
|View full text |Cite
|
Sign up to set email alerts
|

Geologic investigation and mapping of the Sinus Iridum quadrangle from Clementine, SELENE, and Chang’e-1 data

Abstract: The objectives of lunar satellite remote sensing are to study lunar surface characteristics, inner structure, and its evolution history. The contents of TiO 2 and FeO are assessed from Clementine UV/VIS data for Sinus Iridum. The geologic stratigraphic units and crates are interpreted visually based on SELENE Terrain Camera (TC) images and the spatial resolution of which is up to 10 m. And the geologic ages of different stratigraphic units are calculated by the crater size-frequency distributions measurements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Our results of the FeO and TiO 2 contents within the Sinus Iridum region are consistent with those of Bugiolacchi and Guest (2008). Chen et al (2010) suggested that the inner Sinus Iridum region and surrounding highlands are high-iron and medium-titanium, and the Mare Imbrium region is low-iron and high-titanium where the maximum TiO 2 content can be over than 25 wt%. However, both global remote sensing data (e.g., Lucey et al, 1998;Wu et al, 2012) and returned samples data (e.g., Papike et al, 1976) indicate that the mare basalts are more iron-rich than the highland materials and the maximum TiO 2 content of lunar materials is about 14 wt%.…”
Section: Iron and Titanium Abundance Of Mare Basalts Within Sinus Iridumsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results of the FeO and TiO 2 contents within the Sinus Iridum region are consistent with those of Bugiolacchi and Guest (2008). Chen et al (2010) suggested that the inner Sinus Iridum region and surrounding highlands are high-iron and medium-titanium, and the Mare Imbrium region is low-iron and high-titanium where the maximum TiO 2 content can be over than 25 wt%. However, both global remote sensing data (e.g., Lucey et al, 1998;Wu et al, 2012) and returned samples data (e.g., Papike et al, 1976) indicate that the mare basalts are more iron-rich than the highland materials and the maximum TiO 2 content of lunar materials is about 14 wt%.…”
Section: Iron and Titanium Abundance Of Mare Basalts Within Sinus Iridumsupporting
confidence: 87%
“…Considering its flat topography, Sinus Iridum has been selected as one of the important candidate landing areas for the future Chinese robotic and human exploration missions, e.g., Chang'E-5 lunar sample return mission (Qiu and Stone, 2013). Previous studies suggested this region had experienced complex evolutionary history because of the abundant geomorphic features on the surface, including wrinkle ridges, sinuous rilles, impact craters and crater chains, making this region attractive for lunar geology research (e.g., Chen et al, 2010;Gong and Jin, 2012;Huang et al, 2010;Schaber, 1969;Zou, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These features might provide important clues to the formation, basaltic magma intrusion, and late surface modification of Sinus Iridum and Mare Imbrium. In addition to its relatively flat terrain, Sinus Iridum was selected as one of the potential landing sites for CE‐3 lander/rover [e.g., Chen et al , ; Gong and Jin , ; Fa , ].…”
Section: Sinus Iridum Regionmentioning
confidence: 99%
“…This bay and the surrounding mountains are considered one of the most beautiful features on the moon, and is a favorite among lunar observers. The selenographic coordinates of this bay are 44.1°N, 31.5°W, and the diameter is 259 km, with the area of 47750.927 km 2 [18]. Simulation data are applied to analyze the positioning accuracy of the lunar lander, using the software developed at Shanghai Astronomical Observatory (SHAO), Chinese Academy of Sciences.…”
Section: Simulation Results and Analysesmentioning
confidence: 99%